Pengembangan E-Modul Biologi Berbasis Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar pada Materi Virus Kelas X di MA YPKP Sentani - Indah Dwi Rahayu; Tiurlina Siregar; Basa T Rumahorbo (Departement of Mathematics Education, 2024)
This study aims to find out how to make biology e-modules, how to develop biology e-modules, the feasibility of biology e-modules, improve science process skills and learning outcomes using biology e-modules on guided inquiry-based virus material. Research Methods Research and Development. The research sample was carried out in class X MA YPKP Sentani with a total of 37 students. The results of the research show that: 1) How to make e-modules through three stages, namely analysis of potentials and problems, data collection, and product design. 2) How to develop e-modules through four stages, namely define, design, develop, and disseminate. 3) The feasibility of e-module biology obtained an average percentage of eligibility for the material by 95% and the feasibility of the media by 96% with a very feasible category. 4) Assessment of student learning outcomes using e-module biology obtained an average n-Gain of 0.4 in the medium category.